Sandy and clay soils drive ecosystem productivity fluctuations through water limitations - Xinrong Zhu; Lu Wu; Piao Chen (Environmental Research Letters)
Ecosystem water limitation is an important and complicated topic, with soil moisture-driven ecohydrological indicators often yielding contradictory insights into the soils’ impacts on ecosystem water limitation. To address this, we conducted a comprehensive evaluation of two distinct soil-regulated water limitation regimes in global drylands, distinguishing between ecosystem water limitation regulated by wilting point (WP) and those regulated by critical soil moisture (CSM) threshold for meeting ecosystem water demand. We find systematic differences of these two distinct water limitation regimes across drylands: the more significant the WP effect, the less significant the CSM effect, and vice versa. Climatic aridity, soil texture, root-water uptake depths or all together drive the divergence between two types of ecosystem water limitations at regional scale, and soil texture play a dominant role. Sand and clay soils drive ecosystem productivity fluctuations by increased water limitations, albeit through different pathways: clay soils correspond to a more significant water limitation as WP contribution rather than CSM, while sandy soils are the opposite. In this study, the framework of decoupling the differential effects of soil on ecosystem water limitation was re-developed by integrating WP and CSM into ecological drought monitoring and assessment.